Molecular Characterization of Carbapenemase-Producing Pseudomonas aeruginosa of Czech Origin and Evidence for Clonal Spread of Extensively Resistant Sequence Type 357 Expressing IMP-7 Metallo-β-Lactamase - Papagiannitsis, Costas C; Medvecky, Matej; Chudejova, Katerina; Skalova, Anna; Rotova, Veronika; Spanelova, Petra; Jakubu, Vladislav; Zemlickova, Helena; Hrabak, Jaroslav; Czech Participants of the European Antimicrobial Resistance Surveillance Network (Antimicrobial agents and chemotherapy, 2017)
The objective of this study was to perform molecular surveillance for assessing the spread of carbapenemase-producing Pseudomonas aeruginosa in Czech hospitals. One hundred thirty-six carbapenemase-producing isolates were recovered from 22 hospitals located throughout the country. Sequence type 357 (ST357) dominated (n = 120) among carbapenemase producers. One hundred seventeen isolates produced IMP-type (IMP-7 [n = 116] and IMP-1 [n = 1]) metallo-β-lactamases (MβLs), 15 produced the VIM-2 MβL, and the remaining isolates expressed the GES-5 enzyme. The blaIMP-like genes were located in three main integron types, with In-p110-like being the most prevalent (n = 115). The two other IMP-encoding integrons (In1392 and In1393) have not been described previously. blaVIM-2-carrying integrons included In59-like, In56, and a novel element (In1391). blaGES-5 was carried by In717. Sequencing data showed that In-p110-like was associated with a Tn4380-like transposon inserted in genomic island LESGI-3 in the P. aeruginosa chromosome. The other integrons were also integrated into the P. aeruginosa chromosome. These findings indicated the clonal spread of ST357 P. aeruginosa, carrying the IMP-7-encoding integron In-p110, in Czech hospitals. Additionally, the sporadic emergence of P. aeruginosa producing different carbapenemase types, associated with divergent or novel integrons, punctuated the ongoing evolution of these bacteria.
Keywords: Drug Resistance, Multiple, Bacterial; class 1 integrons; karbapenemy; lidé; genomic islands (GIs); integrative conjugative element (ICE); Integrons; Pseudomonas aeruginosa; Gene Expression; nemocnice; antibakteriální látky; beta-laktamasy; Hospitals; beta-Lactamases; Incidence; Pseudomonas Infections; GES; genomové ostrovy; multilokusová sekvenční typizace; Humans; Genotype; Anti-Bacterial Agents; Microbial Sensitivity Tests; Česká republika; bakteriální chromozomy; mikrobiální testy citlivosti; Chromosomes, Bacterial; Carbapenems; Illumina sequencing; integrony; izoenzymy; ST111; ST235; pseudomonádové infekce; Czech Republic; epidemiologické monitorování; exprese genu; genotyp; Multilocus Sequence Typing; incidence; Isoenzymes; VIM; mnohočetná bakteriální léková rezistence; Genomic Islands; Epidemiological Monitoring